Social Computing: A Model of Technology Acceptance to Maintain Micro Enterprise Business During Covid-19 - Diah Gandoriah; Shalu Kumari; Eka Siskawati; Zahara Zahara (Publication Division of International Ecsis Association, 2022)
MSMEs are entrepreneurship growth channels whose existence is recognized as the backbone of national economic development. However, not all MSMEs use technological developments in their business processes. Weak individual skills and expertise as a result of weak mastery of Science and Technology (IPTEK) in a general sense and technological mastery of related products and services in a specific sense. This has an impact on the acceptance of MSME actors for the existence of technology for business continuity, therefore this study aims to see how social computing can affect the technology acceptance model by micro-entrepreneurs in maintaining business. This research is a qualitative research with a phenomenological design. The object of this research is the five people of Padang City micro-entrepreneurs, selected purposively with snowball sampling . Data was collected by means of in-depth interviews and naturalistic observations. This study uses data triangulation to test the validity of the data. The results of this study found that technological efficiency can improve business performance. Besides, the use of technology is able to make the effectiveness of business continuity. The use of technology is also user-friendly when used by users. This study provides implications regarding social computing that occurs between business actors and technology adoption that affects business actors in accepting technology for business resilience.